Confinement of sows for different periods during lactation: effects on behaviour and lesions of sows and performance of piglets. (21st May 2015) - Lambertz, C.; Petig, M.; Elkmann, A.; Gauly, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Alternatives to farrowing crates with continuous confinement of the sow are urgently needed because the animal welfare is negatively impacted. Given the increase of herd sizes, practical experience with loose-housing is needed to force the implementation of these systems in the field. Next to aspects of labour efficiency, detrimental piglet mortality rates that may occur during the first days postpartum (pp) is a major criticism. Therefore, loose-housing after a crating period limited to the first days pp might be a feasible alternative to improve welfare under intensive production conditions. The aim was to investigate the effect of crating sows during lactation for different periods on their behaviour and integument alterations and on piglets' performance. Gilts from a commercial herd were observed from 5 to 26 days pp and housed in farrowing crates (1.85×2.50 m) that could be altered between confinement crates and loose-housing pens. Animals were divided into three groups, that were either crated continuously from birth until weaning (Group A, n=55), until 14 days pp (Group B; n=54) or 7 days pp (Group C, n=59). The behaviour of six randomly selected gilts per group was video recorded from 5 to 26 days pp and analysed by time sampling technique. Lesions on the legs, shoulder and lumbar vertebra were scored on days 7, 14 and 25 pp. Piglets were weighed weekly, causes of losses recorded and weight losses of gilts measured. Not different between groups (P>0.05), animals spent 72 to 76% lying laterally, 14 to 17% lying in abdominal or semi-abdominal position, 9 to 10% standing and 1 to 3% sitting. B-sows were lying longer in week 3 and 4 of lactation compared to A- and C-sows (P<0.05). The incidence of slight shoulder lesions rose from <1% on day 7 to 4% on day 14 and 14% on day 25 pp. On day 25 pp, 5% of all studied gilts showed moderate shoulder lesions. Piglet mortality rates were 11.4%, 12.9% and 13.3% for groups A, B and C, respectively (P>0.05), whereas almost 90% of the losses occurred in the first week pp. In conclusion, loose-housing of lactating gilts after a reduced postnatal crating period of 7 days affected neither the activity level of the gilts and lesions on the integument nor pre-weaning mortality. Therefore, it is recommended to allow sows to move around to some extent during the later lactation period.